Captivating Nepal’s Smartphone Users: The Path to Brand Loyalty - Shrestha, Sajeeb Kumar; Mahat, Dipak; Karki, Tej Bahadur (Nepal Journal of Multidisciplinary Research, 2025)
Background: Understanding brand loyalty drivers is crucial in Nepal's competitive smartphone market. This study investigates five key antecedents; brand image, perceived quality, brand engagement, social media marketing, and customer product involvement proposed to influence brand loyalty, addressing a gap in context-specific research. Methods: A quantitative approach using descriptive and causal research designs was employed. Data from 200 smartphone users in Kathmandu were collected via structured questionnaires, applying convenience sampling. Results: All five hypotheses were significantly supported (*p*<0.05). Customer product involvement emerged as the strongest predictor of brand loyalty, followed by perceived quality and brand image. Brand engagement and social media marketing also demonstrated significant, albeit comparatively weaker, positive effects. Conclusion: The study confirms the multidimensional nature of brand loyalty in Nepal, highlighting customer product involvement as the dominant driver. Brands must prioritize fostering deep consumer involvement with products while strengthening perceived quality, brand image, engagement, and social media outreach to cultivate loyalty. Novelty: Its key novelty lies in revealing customer product involvement not traditional drivers like brand image as the paramount loyalty determinant, offering fresh strategic imperatives for market-specific brand management.